If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10m(5x + -5) = 100 Reorder the terms: 10m(-5 + 5x) = 100 (-5 * 10m + 5x * 10m) = 100 (-50m + 50mx) = 100 Solving -50m + 50mx = 100 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Reorder the terms: -100 + -50m + 50mx = 100 + -100 Combine like terms: 100 + -100 = 0 -100 + -50m + 50mx = 0 Factor out the Greatest Common Factor (GCF), '50'. 50(-2 + -1m + mx) = 0 Ignore the factor 50.Subproblem 1
Set the factor '(-2 + -1m + mx)' equal to zero and attempt to solve: Simplifying -2 + -1m + mx = 0 Solving -2 + -1m + mx = 0 Move all terms containing m to the left, all other terms to the right. Add '2' to each side of the equation. -2 + -1m + 2 + mx = 0 + 2 Reorder the terms: -2 + 2 + -1m + mx = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1m + mx = 0 + 2 -1m + mx = 0 + 2 Combine like terms: 0 + 2 = 2 -1m + mx = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| x^2-10x=-10 | | 123-2x=6x+11 | | 10m(5x-5)m=100 | | 2y-8y+29=5 | | 4(x-9)-8=-44 | | 4x+2=-34 | | -5.4=2.6+2x | | 6x+12=6x+12 | | 2x+5x=7 | | x^4-4x^2-8=0 | | 8x-21-5x=-15 | | 9x-5x+9=1 | | 12(x+6)=10(x+8) | | -32=24y-20 | | 3n-2=2(n-3) | | -5x+9=14 | | 3x^2+2x=110 | | 7-2(3x-4)=5x-18 | | 12(x-4)=72 | | 24x+8=24 | | 1.2m=0.6 | | 392x-98=105 | | 12+2(k+3)=3(k-2) | | 0.25=6 | | x^3+5x^2-8x-12=0 | | x+5.1=13.3 | | x+4x+8x=377 | | -6(-9x-7)= | | 8x-2*49=105 | | 3(x+4)+4=5(x-3)+14 | | 8-2k=-3x | | 7+2+x=8+1 |